Characterization of Natural Convection over an Elliptical Tubes Array AR 2.5 and PR 1.25 inside a Thermally Asymmetric Cavity of Various Clearance Ratio - Stefanus Widhipratama; Budi Utomo Kukuh Widodo (JMES The International Journal of Mechanical Engineering and Sciences, 2018)
Natural convection is the phenomenon of heat transfer due to the buoyancy force of fluid. One application of natural convection inside a vertical cavity is refrigerator condenser of circular cross-section tube. An experimental investigation is presented on natural convection of air over an array of elliptical tubes of AR 2.5 arranged vertically inside a thermally asymmetric cavity. One side of the cavity is insulated and the opposite side is exposed to ambient air. The distance between tubes, pitch ratio PR is constant at 1.25 where “a” is a half of tube major axis. The Clearance Ratio CR which is the ratio between the distance of tubes array major axis to the insulated wall x and the width of the cavity y, is varied 0.4 and 0.6. The heat flux of the tube is maintained at 22.79 kW/m$^2$. It is found that the higher value of heat transfer coefficient is achieved on CR= 0.4.